(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Agriculture is a major driver of deforestation and has a significant influence on deforestation. Because of the enormous population, there is a great need for food, and in order to meet this demand, wide-scale deforestation occurs. Food demand is high, which encourages commercial farming and large-scale land purchase. For large-scale cultivation, forests are being converted to cropland. This has a negative impact on the ecosystem, climate, and human health. Natural habitats and biodiversity are also harmed. This review article examined the influence of agriculture on deforestation while emphasizing the significance of environmental conservation and health. This review included a wide range of topics related to agricultural deforestation. Climate change is currently the most pressing issue facing the globe, which is why it is critical to expand the agriculture sector while also implementing forest preservation policies that will assist to secure and safeguard the environment.